In vitro Production of Secondary Metabolites Reserpine and Ajmalicine in Rauvolfia Serpentina (L.) Benth. - Tiwari, Gyanendra; Tripathi, M. K.; Tiwari, Sushma; Tripathi, Niraj; Uikey, Devi Singh; Patel, R. P. (Current Aspects in Pharmaceutical Research and Development Vol. 4, 2021)
Rauvolfia serpentina is an erect evergreen, woody perennial shrub and usually recognized as Sarpgandha Main institutes of sarpgandha roots are reserpine, rescinnamine, deserpidine and yohimbine and the root part of the plant is employed in several Ayurvedic polyherbal formations viz., sarpgandha vati. When efficient and reproducible plant regeneration systems are available, in vitro culture is an important experimental tool in medicinal and aromatic crops. Experiments were carried out to quantify secondary metabolite production in Rauvolfia serpentina from filtrate of callus and cell suspension cultures. Reserpine and ajmalicine were found infiltrate of both one-month-old callus and cell suspension cultures. The culture medium MSD.5IB (MS+1.0 mgl-1 2,4-D + 0.5 mgl-1 IBA) recovers the most reserpine content in both callus and cell suspension cultures after one month. The amount of reserpine in a liquid medium decreased dramatically as the concentration of 2,4-D in the medium increased. When the concentration of 2,4-D was increased, the concentration of Ajmalicine in both callus and cell suspension cultures decreased linearly. These products may be further produced in commercial scale in bioreactor by using raw biomolecules for commercial purposes.